2016
DOI: 10.1038/srep37941
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial fat oxidation is essential for lipid-induced inflammation in skeletal muscle in mice

Abstract: Inflammation, lipotoxicity and mitochondrial dysfunction have been implicated in the pathogenesis of obesity-induced insulin resistance and type 2 diabetes. However, how these factors are intertwined in the development of obesity/insulin resistance remains unclear. Here, we examine the role of mitochondrial fat oxidation on lipid-induced inflammation in skeletal muscle. We used skeletal muscle-specific Cpt1b knockout mouse model where the inhibition of mitochondrial fatty acid oxidation results in accumulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 77 publications
0
21
0
Order By: Relevance
“…), and genetic ablation of muscle CPT1b (Warfel et al. ) tends to rescue or normalize cell stress‐inflammation phenotypes that accompany inefficient β ‐oxidation or experimental provision of LCFA. These observations highlight excessive LCACs as potential lipotoxins; however, mismatched LCFA availability relative to mitochondrial fatty acid oxidation would increase cellular concentrations of many other lipid derivatives upstream of CPT1, and alter non‐lipid metabolite pools as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and genetic ablation of muscle CPT1b (Warfel et al. ) tends to rescue or normalize cell stress‐inflammation phenotypes that accompany inefficient β ‐oxidation or experimental provision of LCFA. These observations highlight excessive LCACs as potential lipotoxins; however, mismatched LCFA availability relative to mitochondrial fatty acid oxidation would increase cellular concentrations of many other lipid derivatives upstream of CPT1, and alter non‐lipid metabolite pools as well.…”
Section: Discussionmentioning
confidence: 99%
“…CPT1b‐/‐ mice were protected from muscle inflammation under modest fat feeding; in addition, CPT1b‐/‐ myotubes grown in the presence of 500 μ mol/L palmitate plus carnitine displayed >90% lower TNF α and IL6 mRNA levels compared to wild‐type cells (Warfel et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…CRP levels are a clinically relevant marker of subclinical inflammation in obesity and related to metabolic pathways that induces atherosclerosis and diabetes [1]. Moreover, inflammatory cytokines reduces the oxidative capacity of mitochondrial enzymes which favors the accumulation of lipids derivate in peripheral tissue and the lipotoxicity in obesity [29]. In vitro studies revealed that the accumulation of lipid intermediates in peripheral tissues, mainly muscle tissue, leads to low fat oxidation and altered fatty acid metabolism through increased inflammatory pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…in the initiation of the inflammatory processes 30,31 . TLR-2 and TLR-4 activation leads to inflammatory cytokine production such as TNF-α and IL-6 [32][33][34] .…”
Section: Resveratrol Down Regulated Tlr Cascade In Skeletal Muscle Tmentioning
confidence: 99%